"الفكر السياسي الوطني المغاربي ما بين الحربين 1919-1939م " - حمو، دريد, حنانة، السعيد (جامعة الوادي University of eloued, 2018)
"الفكر السياسي الوطني المغاربي ما بين الحربين 1919-1939م يتألّف هذا الموضوع المعنون "" الفكر السياسي الوطني المغاربي ما بين الحربين 1919-1939م"" من مقدمة وفصلين وخاتمة، تناولنا في المقدّمة الخطوات المنهجيّة المطلوبة في الدّراسة، اما الفصلين فكلّ فصل يتكون من عناصر إضافة إلى الملاحق التي لها علاقة بالمتن و بيبلوغرافيا المصادر والمراجع، وفهرس، ولتوضيح ذلك يمكن تقديم عرض مختصر لما احتوته المذكّرة: الفصل الأول بعنوان نشأة الفكر السياسي الوطني المغاربي 1919-1929م وفيه ثلاثة عناصر الاول يخص تونس والثاني الجزائر والثالث المغرب فيه تم التطرق إلى منطلقات الفكر السياسي الوطني بالبلدان المغاربية الثلاثة ومظاهر تشكل الفكر السياسي الوطني فيه حيث كان الافكار الاصلاحية المشرقية رافدا مهما في بروز الفكر الوطني السياسي فيها ، و شكلت النوادي و الجمعيات و الصحف المنطلقات الاولى لتشكل الفكر الوطني السياسي المغاربي و اما عن مظاهر التشكل فتجسدت في بروز التنظيمات الحزبية الاولى و النشاط السياسي للوطنيين المغاربة في الخارج الفصل الثاني جاء عنوانه تطور الفكر السياسي الوطني المغاربي 1930-1939م ، وتم تقسيمه إلى ثلاثة عناصر: تونس، الجزائر، المغرب وتناولنا فيها العوامل المؤثرة في تطور الفكر السياسي الوطني المغاربي و التي أبرزها السياسة الاستعمارية المستفزة و التي تحارب مكنات الهوية الوطنية المغاربية ، إ ضافة الى مخلفات الحرب العالمية الاولى و مبادئ ولسن واهم تطوراته فتمثلت في بروز الفعلي للنشاط الحزبي من خلال المشاركة في الانتخابات و رفع المطالب و تنظيم المظاهرات و عقد المؤتمرات. واختتمنا الدّراسة بخاتمة أوردنا فيها أهمّ النّتائج التي توصّلنا إليها أثناء العمليّة البحثيّة سواء في مستوى التّحليل أو المقارنة لعناصر البحث المدروس." "The National Political Maghrebian Thought between the Two World Wars 1919-1939 This chapter under the title of "" The National Political Maghrebiqn Thought between the Two World Wars 1919-1939"", consists of an introduction, two chapters and a conclusion. In the introduction, we discussed the methodological steps required in the study, while the two chapters consist of elements, in addition to the appendixes related to the material, bibliography of sources and references, and to clarify this via a brief presentation of what contained in the dissertation: The first chapter deals with the emergence of the national political thought in the Maghreb 1919-1929. It includes three elements: Tunisia, Algeria, and Morocco. The first chapter deals with the national political thought of the three Maghrebian countries and the manifestations of national political thought. Clubs, associations and newspapers formed the first starting point to form the national political thought of the Maghreb. As for the forms of formation, they were embodied in the emergence of the first party organizations and the political activity of Moroccan patriots abroad The second chapter was entitled The Evolution of the Maghreb National Political Thought, 1930-1939. It was divided into three elements: Tunisia, Algeria and Morocco, in which we discussed the factors influencing the development of the Maghreb national political thought, which was highlighted by the provocative colonial policy which fights the Maghreb national identity . Besides, the remnants of the First World War and the principles of Wilson and the most important developments were represented in the actual emergence of party activity through participation in the elections and raise demands and the organization of demonstrations and conferences. We concluded the study by concluding with the most important results we reached during the research process, both at the level of analysis or comparison of the research elements have been studied."
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي الحديث والمعاصر
Keywords: الفكر السياسي المغاربي، تاريخ اليهود; Pensée politique du Maghreb, histoire des Juifs; Pensée politique du Maghreb, histoire des Juifs